Pyraclostrobin effect for nitrogen fertilizer efficiency on maize - Setyono Yudho Tyasmoro; Karuniawan Puji Wicaksono; Paramyta Nila Permanasari; Akbar Saitama; Akbar Hidayatullah Zaini (Journal of Degraded and Mining Lands Management, 2019)
Maize is one of the food crop commodities that can take a role in the development of the agricultural sector. The purpose of this research was to know the effect of pyraclostrobin and nitrogen on the maize plant. The experimental design used in this study was a factorial completely randomized block design with three replications. The first factor was pyraclostrobin (P) that consisted of P0 = no pyraclostrobin application, and P1 = foliar spray of pryraclostrobin 400 mL/ha. The second factor was nitrogen application (N) that consisted of N0 = without N fertilizer, N30 = 30 kg N/ha, N60 = 60 kg N/ha, N90 = 90 kg N/ha, and N120 = 120 kg N/ha. The data was focused on the plant height, flowering and earing age, protein and amylose content of the seed, respectively. Data were analyzed by variance analysis followed by. analysis of the least significant difference (LSD) at the level of 5%. Nitrogen application increased protein content but reduced amylose content. Pyraclostrobin application that significantly increased the amylose content even in the high nitrogen application dosage